Continued breastfeeding: Prevalence and causes for weaning in children under two years of age (Revista Contexto & Saúde, 2025)
The objectives of this study were to estimate the prevalence of continued breastfeeding in the second year of life of children who were exclusively breastfed in the first six months and to describe the reasons for interrupting breastfeeding before the age of two years of these children. This is a cross-sectional analysis of a longitudinal study conducted at the Fernandes Figueira Institute (IFF) of the Oswaldo Cruz Foundation (FIOCRUZ), located in Rio de Janeiro, Brazil. The research sample consisted of 122 children born at the IFF or who were transferred to the unit up to seven days old. Data was collected in the second year of life of these children through 17 open and closed questions asked by telephone contact with their respective mothers and the data were then descriptively analyzed in the R software program. Approximately 40% of the mothers were not breastfeeding in the second year of life and some of the reasons cited were the child’s refusal to breastfeed, fatigue, return to work and insufficient breast milk. Considering the demands presented, it is understood that weaning before two years of age is not caused by just one, but many factors during the first 24 months. Therefore, it is important that health professionals are made aware and trained, especially with regard to encouraging breastfeeding after the exclusive period, as this is influenced by multiple factors and requires comprehensive monitoring of the mother-baby binomial.
Keywords: continued breastfeeding; child health; weaning